Efficacy of docusate in the treatment of constipation in pediatric patients - Saif, Hamsah; Maddula, Tanay; Mendelsohn, Kerry; Akerman, Meredith; Sweeney, Nicole; Noyola, Estela; El-Chaar, Gladys (Frontiers in Pediatrics, 2025)
ObjectivesWe hypothesized that docusate is effective in the treatment of constipation in pediatric patients. Secondary outcomes included the safety and acceptance of docusate as well as the efficacy, safety and acceptance of PEG-3350 in the treatment of constipation.MethodsThis multicenter retrospective study included children 1 month to 18 years of age who received either oral docusate or PEG-3350 during their hospital admission. We documented the occurrence of bowel movements within the first 72 h of drug administration. We also evaluated time to first bowel movement, frequency of bowel movements per 24-hour periods, adverse effects and acceptance of docusate/PEG-3350 by the patients, concomitant medications, and response according to medical history.ResultsThere were 90 patients in each of the docusate and PEG-3350 groups. Bowel movements occurred within 72 h in 66.67% in the docusate group and 71.11% in the PEG-3350 group. There was no significant difference between the groups (p = 0.5196). The time to achieve first bowel movement was not different between groups (48.9 h vs. 45.4 h, docusate and PEG-3350, p = 0.3283). There were no differences in adverse effects or acceptance between groups.ConclusionsThis is the first study that proves the efficacy of oral docusate in the treatment of hospitalized pediatric patients with acute constipation. It is also the first study that shows no difference in efficacy between docusate and PEG-3350 in pediatric patients. We hope a prospective trial would further confirm our findings.